TAAT KYAI: Tradisi Pernikahan Santri dalam Perspektif Maqasid Shariah - Ahmad Masruh; Ahmad Zahro (LPPM UNHASY, 2021)
This article is the result of a qualitative field research. The research location is at the At-Tahdzib Islamic Boarding School Rejoagung Ngoro Jombang. The direction of the discussion in this article is how to place the marriage tradition following the Kyai within the framework of maqasid marriage and maqasid shariah. The researcher uses maqasid al-nikah and maqasid shariah theory in explaining the position of the marriage tradition following the Kyai, because the maqasid al-nikah and maqasid shariah theories. The researcher argues that the marriage tradition following the Kyai provides advocacy for the protection of the bride and groom in achieving the goals of marriage and the goals of the Shari'a that arise from marriage Keywords: marriage is obedient to the kyai, maqasid shariah. DAFTAR PUSTAKA Amin, H. A., Masrokhin, M., & Anwar, K. (2021). GUARDIANS CONCEPT IN QUR’AN PERSPECTIVE . SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam , 6(1), 95 - 114. https://doi.org/10.33752/sbjphi.v6i1.1642 Abu, Badran Al-Ainai, al-Fiqh al-Muqaran li al-Ahwal al-Syakhshyiah, Beirut: Dar Fikr. Ahmad, Ali al-Jurjani, 1994, Hikmah al-T asyri’ wa Falsafatuhu, jilid II. Beirut: Dar Fikr. ‘Ali Muhammad al Sabu>ni, 2008, Ayat Ahkam Rawa>I’ul Bayan, ter . Mu’amal Hamidi dan Imron Manan, Surabaya: Bina Ilmu. Husain, Ahmad Al-Musri Al-Jauhar, Cet 2. 2010. Maqashid Syariah, Terjemah oleh Khikmawati, Jakarta: Amzah. Katherine Miller, John and Foss, 2012, Theories of Human Communication . Kusujiarti, Siti, 1995, Hidden Power in Gender Relations Among Indonesia: a Case Study in Javanese Village, Indonesia, Kentucky: University of Kentucky. Mandzur, Ibnu. Cet 1. 2003, Lisa>n al-‘Arab. Juz 3, Libanon: Dar al-Kutub al-Ilmiyah. Muhammad, Abu> ‘Isa Al-Turmu>dzi, 1996, Sahih Sunan Tirmi>dzi, Jus 3 Beirut: Da>r al Ghorbi al Islamy. Muhammad, Abu> ‘Abdillah bin Yazi>d a l Ghuzwaini, 2001, Sunan Ibn Majah, Juz, 1 Beirut: Da>r al Ihya. Mudzhar. Cet. III, 2001, Pendekatan Studi Islam: dalam Teori dan Praktek, Yogyakarta: Pustaka Pelajar. Muhtarom, Ali, 2015, Kafa>’ah Dalam Perkawinan (Telaah Atas Pemikiran Ibnu Hazm Terhadap Keberlakuan Kafa>’Ah Dalam Hukum Perkawinan) Newman, W. Lawrence, 4th edition, 2000, Social Research Methods, Qualitative and Quantitative Approaches, Needham Heights USA: Allyn & Bacon. Syaltout, Mahmud.1966, Islam: ‘Aqidah wa Syari’ah. Kairo: Dar al-Qalam. Zuaili, Wahbah, 1985, al-Fiqhu al-Islamii wa Adillatuhu, Juz 7. Beirut: Dar al-Fikr. Zarnuji, Imam, 2003, Ta’l Muta’alim, Surabaya: al Hidayah.